The Impact of Psychological Empowerment on Workaholism - Hassan, Masood; Azmat, Urooj; Uddin, Imam (Nurture, 2018)
The objective of this study was to investigate the impact of psychological empowerment on workaholism among University faculty. Two hypotheses were tested: 1) There is an impact of Psychological Empowerment on Workaholism. 2) There is a gender difference in Psychological Empowerment and Workaholism. The current study followed the quantitative research approach by using the convenience sampling technique. Data was collected from the 40 faculty members of one public and one private university located in Karachi. For the data collection, two scales were used i.e. Psychological Empowerment by Spreitzer (1995) Instrument, and “Workaholism analysis questionnaire”. The study findings suggested that the impact of Psychological empowerment on Workaholism is not significant and there was no gender difference in these two variables. The findings of this study can contribute to the educational sector by enhancing the understanding association between Psychological Empowerment and workaholism among Faculty staff.